2023
DOI: 10.3389/fonc.2022.1077792
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of geriatric nutritional risk index on patients with urological cancers: A meta-analysis

Abstract: BackgroundDespite previous research examining the predictive value of the geriatric nutritional risk index (GNRI) in individuals with urological cancers (UCs), results have been conflicting. This study aimed to comprehensively explore the potential link between GNRI and the prognosis of UCs using a meta-analysis.MethodsThe Cochrane Library, PubMed, Embase, and Web of Science databases were systematically and exhaustively searched. We estimated the prognostic importance of the GNRI in patients with UCs by calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Recent meta-analyses have reported that the GNRI significantly predicts cancer prognosis (34)(35)(36)(37)(38). Zhang et al conducted a meta-…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent meta-analyses have reported that the GNRI significantly predicts cancer prognosis (34)(35)(36)(37)(38). Zhang et al conducted a meta-…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis involving 3,440 participants showed that a lower GNRI before treatment predicted poorer OS and disease-free survival of colorectal cancer cases ( 40 ). Another meta-analysis enrolling 6,792 patients indicated that a lower GNRI strongly estimated dismal OS, RFS/PFS, and CSS in urological cancers ( 38 ). According to Wang et al., a low GNRI predicted dismal OS, RFS, and CSS in lung cancer cases ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous meta-analyses have investigated the GNRI's prognostic value in human malignancies, including in esophageal cancer, 18 pancreatic cancer, 36 lung cancer, 37 urological cancer, 38 and colorectal cancer. 39 In line with those of the aforementioned studies, the results of our study support that the GNRI is a valuable prognostic indicator for patients with HNC.…”
Section: Discussionmentioning
confidence: 99%